2021
DOI: 10.1097/cad.0000000000001262
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 47 promotes cell migration and invasion through AKT signal in non-small cell lung cancer

Abstract: Lung cancer is one of the most lethal malignancies, with the highest number of cases and deaths. Non-small cell lung cancer (NSCLC) is the most ordinary type of pathology in lung cancer. Meanwhile, various researchers have reported that heat shock protein 47 (HSP47) plays a vital regulatory role in cancer. However, the role of HSP47 in NSCLC is not clear. Consequently, the current study set out to investigate the role of HSP47 in the pathogenesis of NSCLC. First, we evaluated the expression patterns of HSP47 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…22 Loss-of-function studies based on shRNA against HSP47 revealed that HSP47 contributes to proliferation, migration, and invasion of lung cancer cells. 10 In gastric cancer, HSP47-silenced cells demonstrated reduction in WNT/β-catenin signaling pathway proteins, including Snail1, Slug, and TWIST, which control epithelial-mesenchymal transition, culminating in decreased cell migration and invasion. 9 Our data did not demonstrate that HSP47 knockdown alters OSCC cell survival or sensitize cells to cisplatin, in spite of HSP47 levels has been correlated to tumor progression and response to chemotherapy in glioblastomas, 27 and overexpression of HSP47 conferred chemoresistance to 5-fluorouracil in colorectal cancer 5 and to gemcitabine, a nucleotide analog included in the multidrug chemotherapy regimen in many tumor types, in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 Loss-of-function studies based on shRNA against HSP47 revealed that HSP47 contributes to proliferation, migration, and invasion of lung cancer cells. 10 In gastric cancer, HSP47-silenced cells demonstrated reduction in WNT/β-catenin signaling pathway proteins, including Snail1, Slug, and TWIST, which control epithelial-mesenchymal transition, culminating in decreased cell migration and invasion. 9 Our data did not demonstrate that HSP47 knockdown alters OSCC cell survival or sensitize cells to cisplatin, in spite of HSP47 levels has been correlated to tumor progression and response to chemotherapy in glioblastomas, 27 and overexpression of HSP47 conferred chemoresistance to 5-fluorouracil in colorectal cancer 5 and to gemcitabine, a nucleotide analog included in the multidrug chemotherapy regimen in many tumor types, in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of HSP47, which was expressed in high levels in TE‐8 cells, an esophageal cancer cell line, significantly inhibited proliferation and colony formation, conferring an oncogenic potential on esophageal squamous cell carcinoma 22 . Loss‐of‐function studies based on shRNA against HSP47 revealed that HSP47 contributes to proliferation, migration, and invasion of lung cancer cells 10 . In gastric cancer, HSP47‐silenced cells demonstrated reduction in WNT/β‐catenin signaling pathway proteins, including Snail1, Slug, and TWIST, which control epithelial–mesenchymal transition, culminating in decreased cell migration and invasion 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aberrant expression of the SERPINH1 gene has been shown to be closely linked to tumor growth, invasion, and metastasis in cervical squamous cell carcinoma and gastric cancer [ 65 , 66 ]. In non-small cell lung cancer cell lines, HSP47 was highly expressed, whereas the inhibition of HSP47 repressed cell migration and invasion by diminishing the AKT signal [ 67 ].…”
Section: Relationship Between Hsp47 and Pulmonary Fibrosismentioning
confidence: 99%